Synthesis and Characterization of Alkali Free Mg-Al Layered Double Hydroxide for Transesterification of Waste Cooking Oil to Biodiesel: Effect of Mg/Al Ratio - Hafiza Ibrahim, Erma; Ahmad Tajuddin, Nazrizawati; Hamzah, Noraini (International Journal of Engineering and Technology, 2019)
The depletion of fossil fuels and the concerned toward environmental sustainability have created a considerable to alternate development of sources of energy as substitute for traditional fossil fuels. The biodiesel production has been reported to be an ideal solution as alternative diesel fuel due to its environmental benefits. Thus, the transesterification of waste cooking oil with methanol in the presence of Mg-Al layered double hydroxide (LDHs) as a heterogeneous catalyst was studied to produce the biodiesel. In this work, Mg-Al-LDH was fabricated via alkali free co-precipitation method with final Mg/Al ratio of 4:1, 3:1 and 2:1. The product of co-precipitation was undergone aging process for 24 h. Then it was placed in oven at 100 â°C overnight and finally was calcined at 450 â°C for 5 h. The correlation of crystallinity, morphology and particle size of Mg-Al-LDH before and after calcined were examined and compared. X-ray diffraction analyse (XRD) was used to study the textural and structural characteristics of the samples. Particle size, morphology and particle properties were characterize by Brunauer, Emmett and Teller (BET) and Scanning electron spectroscopy (SEM). The bonding and structural of Mg-Al-LDH was studied by Fourier transform infrared spectroscopy (FTIR). Energy dispersive X-ray spectroscopy (EDX) was used for the elemental analysis of the samples. The catalytic activity was evaluated by the transesterification reaction under the following reaction condition: temperature (60 â°C-65 â°C), time (24 h) and methanol to oil ratio (15:1) .The greatest yield was 85.2% and obtained with combination of 4:1 Mg/Al ratio followed by 3:1 and 2:1 ratio.Â Â